2019
DOI: 10.19027/jai.18.1.46-53
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zinc (Zn) supplementation on quality and quantity of striped catfish Pangasianodon hypophthalmus sperm

Abstract: This study aimed to evaluate the effects of Zinc (Zn) supplementation on the quality and quantity of striped catfish sperm. Experimental design for this study was a complete randomized design with five treatments and five replications. Male broods fed with Zn supplementation for eight weeks. The Zn supplemented into the fish diet at different concentrations (0, 50, 100, 150 and 200 mg/kg of feed). The results showed that Zn supplementation could improve the quality and quantity of striped catfish sperm. The tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…This influence on viability and motility is due to the Zn action on lipid catabolism, functioning as the source of energy for spermatozoa motility [ 45 ]. A study performed on catfish ( Pangasianodon hypophthalmus ) [ 51 ] revealed that feed supplementation with 200 mg/kg of Zn could improve sperm concentration and volume over 50% and percentages of sperm motility and viability were also significantly higher than with other treatments. In a different experiment, Aripin, et al [ 52 ] supplemented the diets with a combination of melatonin and zinc and showed that this mixture could reduce the abnormalities on spermatozoa and increase some kinetics parameters, such as sperm motility, concentration, and lateral amplitude.…”
Section: Fish Sperm Antioxidant System and Supplementation: Classimentioning
confidence: 99%
“…This influence on viability and motility is due to the Zn action on lipid catabolism, functioning as the source of energy for spermatozoa motility [ 45 ]. A study performed on catfish ( Pangasianodon hypophthalmus ) [ 51 ] revealed that feed supplementation with 200 mg/kg of Zn could improve sperm concentration and volume over 50% and percentages of sperm motility and viability were also significantly higher than with other treatments. In a different experiment, Aripin, et al [ 52 ] supplemented the diets with a combination of melatonin and zinc and showed that this mixture could reduce the abnormalities on spermatozoa and increase some kinetics parameters, such as sperm motility, concentration, and lateral amplitude.…”
Section: Fish Sperm Antioxidant System and Supplementation: Classimentioning
confidence: 99%
“…It is also responsible for production, storage and secretion of hormones, maintenance of immune system and electrolyte balance (Mcdonald et al, 2007). It is found in high concentration in the male reproductive tract as well as in semen (Chia et al, 2000) and plays a very important role in male fertility as it acts as hormone receptor modulator for testosterone in Leydig cell leads to maintenance of sperm production and quality (Roy et al, 2013;Kaliky et al, 2019). Zn deficiency affects the DNA synthesis in the germ cell, sperm formation and also reduce the sperm motility (Yamaguchi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Zn is a mineral element that is mostly accumulated in bones compared to liver as the main organ of micro mineral preservation (Setiawati et al, 2007) and as a cofactor in bone formation (Yamaguchi, 2010). Kaliky et al (2019) reported that Zn also played an important role in the reproduction process of striped catfish.…”
Section: Introductionmentioning
confidence: 99%